2017
DOI: 10.1080/01457632.2017.1295738
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Heat Transfer in Partially Heated Vertical Channel Under Mixed Convection by Using Al2O3 Nanoparticles

Abstract: Laminar mixed convection in a two-dimensional symmetrically and partially heated vertical channel is investigated. The heaters are located on both walls and uniform temperature is applied on the heated sections. The number of heaters is considered as 1, 4, 8, and 10. Aluminum oxide/water nanofluid is considered as working fluid and the inlet velocity is uniform. The continuity, momentum and energy equations with appropriate boundary conditions are solved in dimensionless form, numerically. The study is perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Dogonchi et al (2020) numerically investigated the effects of nanoparticles shape factors on natural convection in a porous annulus filled with a nanoliquid formed between the elliptical cylinder and square enclosure. A comprehensive investigation was performed by Celik et al (2018) on the flow behavior of nanofluid combined mixed convection inside a partially heated vertical channel, and the obtained results are useful to design a new system that use nanofluid in cooling of partially conductive walls. In the same context, Da Silva et al (2005) and Bazylak et al (2006) analyzed the most effective way to distribute discrete heat sources that are cooled through Cooling performance of electronic components natural convection in channels and enclosures.…”
Section: Hff 342mentioning
confidence: 99%
“…Dogonchi et al (2020) numerically investigated the effects of nanoparticles shape factors on natural convection in a porous annulus filled with a nanoliquid formed between the elliptical cylinder and square enclosure. A comprehensive investigation was performed by Celik et al (2018) on the flow behavior of nanofluid combined mixed convection inside a partially heated vertical channel, and the obtained results are useful to design a new system that use nanofluid in cooling of partially conductive walls. In the same context, Da Silva et al (2005) and Bazylak et al (2006) analyzed the most effective way to distribute discrete heat sources that are cooled through Cooling performance of electronic components natural convection in channels and enclosures.…”
Section: Hff 342mentioning
confidence: 99%
“… * constant value; remark: if using dimensionless numbers, the ranges are based on common academic proposals in the literature [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. …”
Section: Figurementioning
confidence: 99%
“…Celik et al [ 9 ] numerically investigated the heat transfer enhancement within a vertical channel, where a nanofluid passes through. The results showed that the heat transfer rate would enhance by increasing the Reynolds and Richardson numbers and adding 5% of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by declining the thermophoresis parameter, a rise in both temperature and concentration profiles were seen. Celik et al 14 researched heat transfer in the form of natural and forced convection of a nanofluid with Al2O3 for nanoparticles in a channel. It was verified that the Nusselt number is enlarged by adding nanoparticles to the primary fluid at a rate under the effect of several factors, such as Reynolds and Richardson numbers.…”
Section: Introductionmentioning
confidence: 99%